2020
DOI: 10.1038/s41598-020-58676-2
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic properties of a phytase producing Pediococcus acidilactici strain SMVDUDB2 isolated from traditional fermented cheese product, Kalarei

Abstract: The nutritional challenge faced by the monogastric animals due to the chelation effects of phytic acid, fuel the research on bioprospecting of probiotics for phytase production. Pediococcus acidilactici SMVDUDB2 isolated from Kalarei, exhibited extracellular phytase activity of 5.583 U/mL after statistical optimization of fermentation conditions viz. peptone (1.27%); temperature (37 °C); pH (6.26) and maltose (1.43%). The phytase enzyme possessed optimum pH and temperature of 5.5 and 37 °C, respectively and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…For assessment their safety, they were tested for susceptibility to ten antibiotics where they showed susceptibility or intermediate to seven antibiotics; the gram-positive spectrum antibiotic erythromycin, the broad-spectrum antibiotics tetracycline and the aminoglycosides gentamicin, amoxicillin and co-trimoxazole in addition to kanamycin and chloramphenicol these results are in agreement to previous results on LAB [48,49]. They all were resistant only three antibiotics; vancomycin in agreement to the results obtained by Singla et al [50] and Bhagat et al [45] in addition to ampicillin, ciprofloxacin.…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…For assessment their safety, they were tested for susceptibility to ten antibiotics where they showed susceptibility or intermediate to seven antibiotics; the gram-positive spectrum antibiotic erythromycin, the broad-spectrum antibiotics tetracycline and the aminoglycosides gentamicin, amoxicillin and co-trimoxazole in addition to kanamycin and chloramphenicol these results are in agreement to previous results on LAB [48,49]. They all were resistant only three antibiotics; vancomycin in agreement to the results obtained by Singla et al [50] and Bhagat et al [45] in addition to ampicillin, ciprofloxacin.…”
Section: Plos Onesupporting
confidence: 89%
“…revealed that all of them belong to P. acidilactici strains available in the database by 100% identical. Our three strains named as P. acidilactici WNMY01, P. acidilactici WNMY02 and P. acidilactici WNMY03 met the probiotic criteria by expressing tolerance to alkaline condition (pH 9.0) 95% survival and to bile salt by giving > 90% survival to 0.7% bile salt for 24 hours and > 50% survival to 2% bile salt for 3 h these results are competing to P. acidilactici B14 showed 72.4% in 0.3% bile salt [44] while P. acidilactici SMVDUDB2 showed 80% at 0.3% -0.5% bile salt [45]. Furthermore, our three strains showed antibacterial activity against the four tested bacteria; the gram positive (B. subtilis and S. aureus) as well as the gram negative (E. coli and P. aeruginosa).…”
Section: Plos Onementioning
confidence: 99%
“…Pediococcus acidilactici strains have been widely studied in food and feed applications. For instance, P. acidilactici SMVDUDB2 [ 14 ] was found to be capable of phytate degradation and to possess probiotic traits, which can be useful in food and feed applications. Interestingly, probiotic P .…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that the use of starter culture in fermented foods in order to improve the quality and produce safe food compared with spontaneous fermentation. P. acidilactici strains have key enzymes involved in homo-fermentation including D- and L- lactate dehydrogenases [ 14 ]. Therefore, they can quickly produce lactic acid to reduce fermentation time.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance against bile acid and low pH, ability to adhere to the mouse intestinal epithelium cells, and protective role against the invasion of Salmonella in mouse liver and spleen Chiu et al, 2008 Dairy products (fermented and nonfermented) Pediococcus acidilactici SMVDUDB2 Kalarei, a fermented cheese product 80% survival rate at pH 2.0 and 3.0 and 0.3% bile salt concentration, high hydrophobicity affinity (33%) with ethyl acetate, autoaggregation (77.6%), antibacterial activity against Bacillus subtilis, Mycobacterium smegmatis, Staphylococcus aureus, Proteus vulgaris, and Escherichia coli, and EPS production (2 g/L) Bhagat et al, 2020 Enterococcus lactis…”
Section: Pickled Vegetablesmentioning
confidence: 99%